Molecular characterization of peroxisome proliferator activated receptor gamma2 (PPARγ2) promoter from bovine - Ismail, Ida Shazrina; Mat Arip, Yahya; Tengku Muhammad, Tengku Sifzizul (2004)
Peroxisome proliferator activated receptor gamma (PPARγ) is a member of the PPAR subfamily of nuclear hormone receptors (Schoonjans et al., 1996a). So far, two PPARγ isoforms; γ1 and γ2, have been cloned in bovine and produced by alternative promoter usage and differential splicing of a single gene (Sundvold et al., 1997). PPARγ functions by forming heterodimeric complexes with 9-cis-retinoic acid X receptors (RXRs). This heterodimer regulates transcription by binding to PPRE, known also as DR-1 response element in the regulatory regions of target genes (Tontonoz et al., 1994a).